ANALISIS PENERIMAAN PBB KABUPATEN / KOTA PROVINSI JAWA TENGAH PERIODE 2009 - 2013 - Yunarsih, Yunarsih; Masdjojo, Gregorius N (Jurnal Ilmiah Telaah Manajemen, 2015)
The objectives of this research is to know the impact of the Value of Tax Object and thechange of Tax Object to the Domestic Product of Regional Bruto in Central Java Province. Then this research also to know the impact of the Value of Tax Object, the change of Tax Object and Domestic Product of Regional Bruto to the acceptance of Land and Building Tax in Central Java Province. This research take data from 35 District/City on the period 20092013. The data analyzed by panel data regression technique. This research found that the Value of Tax Object has a significant positive effect to the Domestic Product of Regional Bruto and the Change of Tax Object has significant positive effect on Domestic Product of Regional Bruto. the Value of Tax Object, Change of Tax Object and Domestic Product of Regional Bruto partially have a significant positive effect to the acceptance of Land and Building Tax. But Domestic Product of Regional Bruto is not the intervening variable on the relationship between Change of Tax Object and the acceptance of Land and Building Tax.Keywords : the value of tax object, the change of tax object, domestic product of regional bruto and the acceptance of land and building tax